Management not models: adaptability, responsiveness, and a few lessons from football - Maclay, Christopher (Development in Practice, 2015)
Despite a swathe of critiques of logframes and other blueprint approaches to development over the last 30 years, most aid infrastructure continues to concentrate on the design and subsequent implementation of closed models. This article does not propose an alternative to blueprints, but challenges the inflexibility of their implementation, which is inadequate given the complex nature of social change. It proposes a supplementary management and learning approach which enables implementers to be dynamic, adaptive, and responsive to problems and opportunities. Emphasising the role of donors, the paper presents a case study of one donor-led programme in Bangladesh doing just this.

Logics of Government Innovation and Reform Management in China - Husain, Lewis (STEPS centre, 2015)
Since the beginning of reforms in the late 1970s, China has developed rapidly, transforming itself into a middle-income country, raising hundreds of millions out of poverty and, latterly, developing broad-based social protection systems. The country’s approach to reform has been unorthodox, leading many to talk of a specific Chinese model of development. This paper analyses the role of innovation (chuangxin) and experimentation in the Chinese government repertoire and their contribution to management of change during the rapid, complex and interconnected reforms that China is undergoing. ‘Innovation’ is understood as the process of generation, putting into use, and spread, of new ideas. This contemporary focus on innovation is an extension of an older Chinese government attachment to sub-national initiative in policy formulation and development that goes back to the beginnings of the PRC and before. Central government backing for, and endorsement of, proactive agency on the part of sub-national governments responds to a belief that China is too large, and conditions around the country too diverse, to allow adoption of ‘one size fits all’ policy. Sub-national governments are expected to show initiative in adapting policy locally, and creating locally-useable policy solutions within the overall scope of central policy mandates/ paradigms. The paper argues that innovation by sub-national government is systemically embedded: while central government sets the policy agenda, local governments are frontline managers, and develop a range of policy practices. Differences in conditions between localities mean that multiple variant policy practices are often in circulation at any one time. While innovation is not quantifiable in the aggregate, there is much controlled experimentation, freewheeling innovation, and trial and error, all of which are part of a search for new policy fixes and institutional solutions. Many forms of policy transfer and learning are in evidence, including much central learning from sub-national models, as well as sub-national circulation of a range of innovative policy practices. While much government innovation is not ‘original’, and may be ‘inefficient’ or of little systemic usefulness, overall, the churn of government innovation remains valuable in underpinning systemic adaptation and reform. The paper situates the analysis of government innovation within a larger framework on the functioning of Chinese government and international literature on policy transfer, and outlines an agenda for future research on the structural bases of Chinese government innovation and its contribution to adaptive management.

SAVI Approach Paper 5: Defining and Measuring Results - SAVI (DFID, 2015)
SAVI aims to facilitate replicable and sustainable processes of citizen engagement in governance. The programme in each state is locally defined, flexible and adaptive, and results are not predictable in advance. Standardised monitoring tools are not applicable, and consequently we have evolved our tools and frameworks during the programme through processes of learning by doing....

Monitoring and Adaptive Management - Ossi, Damien (District of Columbia Wildlife Action Plan - 2015, 2015)

2015 Rhode Island Wildlife Action Plan - Chapter 5 Monitoring and Adaptive Management - Terwilliger Consulting (State of Rhode Island, 2015)

Enabling citizen-driven improvement of public services. Leveraging Technology to Strengthen Accountability in Nigerian Healthcare - ICT4SA (World Bank and Reboot, 2015)
Effective public service delivery begins with knowing whether the services offered are working as intended. We launched a system to enable citizen input on the delivery of public services.

SAVI Approach Paper 1: Core Values - SAVI (London, 2015)
Governance reform is about government and citizens working together in more responsive, inclusive and accountable ways for the benefit of citizens. More responsive, inclusive and accountable attitudes and behaviour on the part of government and non-government stakeholders are the critical factors which lead to meaningful reform processes, and replicate and sustain reforms beyond the lifetime...

SAVI Approach Paper 2: Programme Design - SAVI (DFID, 2015)
SAVI supports citizen engagement in governance through a facilitated partnership approach, in contrast to the usual approach of grants to civil society organisations (CSOs). The overall aim is to facilitate and support working relationships and processes of reform that are home-grown, self-sustaining and, after initial engagement, not dependent on external support. Our way of working...

SAVI Approach Paper 3: Theory of Change - SAVI (DFID, 2015)
SAVI’s theory of change is a simple, practical guide that staff and partners use to plan and to monitor change – as well as to reflect on and enhance their own effectiveness. It sets out broad stages of attitude and behaviour change over time to facilitate effective citizen engagement in governance processes, systems and structures....

SAVI Approach Paper 6: Engaging Civil Society - SAVI (DFID, 2015)
SAVI state teams provide support to CS groups to become more effective agents of citizens’ voice and public accountability, through a variety of mutually reinforcing interventions. These include: hands-on support to demonstration civil society Advocacy Partnerships (APs) facilitating working partnerships between civil society APs, SHoAs, and the media brokering working relationships between all of these...

SAVI Approach Paper 7: Promoting Gender Equality and Social Inclusion - SAVI (DFID, 2015)
We promote attention to gender equality and social inclusion in all of our engagement with CS groups, the media and SHoAs, and in all of the issues and processes they work on. In all the states we work in, we also support partners to focus on some issues and form some partnerships and networks which...

SAVI Approach Paper 8: Engaging the Media - SAVI (DFID, 2015)
The overall aim of SAVI engagement with the media is for media representation of citizens’ interests to become normal, and play its part in helping state governments to be more responsive, inclusive and accountable to their citizens. Media partners – individual media personnel and selected media houses – are supported to be more effective agents...

SAVI Approach Paper 9: Engaging State Houses of Assembly - SAVI (DFID, 2015)
The overall aim of SAVI engagement with SHoAs is to promote lasting reforms that are not dependent on external funding and which promote an increasingly more responsive and accountable relationship between Nigerian state governments and their citizens. SHoAs are supported to be more effective agents of citizen voice and public accountability, demanding better performance from...

SAVI Approach Paper 10: Engaging State Governments - SAVI (DFID, 2015)
SAVI as a programme does not directly work with state governments – but we work in close conjunction with sister programmes who are supporting state governments on governance and sector reforms. SAVI supports non-government and SHoA partners to play their part in promoting more responsive, inclusive and accountable state governance delivering better services for citizens....

Introduction to SAVI's way of working - State Accountability and Voice Initiative (SAVI) - SAVI (DFID, 2015)
We are piloting a new approach to identifying and supporting our partners.  This breaks with convention in many ways in order to improve impact.  SAVI Approach Papers summarise key aspects of SAVI’s way of working. They explain what we do, and why – and link to relevant tools and frameworks. Our approach is summarized in...
Keywords: Practice

SAVI Approach Paper 4: Thinking and Working Politically - Supporting partners and staff through a participatory apporach to political economy analysis - SAVI (DFID, 2015)
Thinking and acting politically is central to the SAVI programme. We support staff and partners to analyse the power relations that shape change in their state, and to use this knowledge to inform their decision-making. This includes decisions made by SAVI state teams relating to the issues and partners they engage with and support, and...